A prospective, population-based, surveillance (BOSU) study of uveal effusion syndrome in the UK. Issue 5 (September 2021) - Sharma, Rohit; Foot, Barny; Jackson, Timothy L
Purpose: To determine the incidence and demographic profile of uveal effusion syndrome (UES), and to describe the visual and anatomic outcome following deep sclerectomy or vortex vein decompression. Methods: The British Ophthalmological Surveillance Unit (BOSU) mails reporting cards monthly to 1149 senior UK ophthalmologists, who are requested to report incident cases of specified rare diseases. UES was included in the reporting system from October 2009 to October 2011. If UES was identified, ophthalmologists were mailed a questionnaire to collect anonymized clinical data at baseline, and 12 months after. Results: Over 2 years, 29 cases were reported. Two cases were duplicates and 12 failed to meet the eligibility criteria. Of the 15 eligible cases, age ranged from 11 to 91 years (mean 62) and nine were males (60%). Ten patients were hypermetropic; three had an axial length of 19.0 mm or less. Estimated annual incidence was 1.2 per 10 million population. Seven cases were managed nonsurgically, including observation (one case), topical steroids (two cases), systemic steroids (three cases), and cyclodiode laser (one case). Eight cases (11 eyes) underwent full-thickness sclerectomy; the elevated flap was retained in four. The sclera was noted to be thick and rigid during surgery in five cases. Median preoperative visual acuity was 6/18, changing slightly to 6/21.5 at final review, with three eyes showing complete anatomic response, five showing some improvement, and three failing to respond. Conclusions: UES is extremely rare. It occurs in a range of ages, but is most common in middle-aged, hypermetropic men. Visual acuity can be materially reduced. The most commonly used surgical treatment in the UK is deep sclerectomy.